Coaxial Multiplexer For Automatic Measurementof Ac Current - Boštík, Ondřej (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
The paper presents recent work on measurement automatization at the Czech Metrology Institute (CMI) in Brno. The purpose of designed equipment is to automatically switch current shunts during the calibration procedure of precise current sources. The article presents some of the main components including voltage follower and coaxial multiplexer itself and the final solution.
Keywords: CMI; current measurement; measurement axiomatization; calibration; voltage follower; shunts switch